The National Battery Research Institute: Energizing Indonesia’s Battery Revolution on Skills Development - Mubarok, Moh. Wahyu Syafi'ul; Yogandini, Rosi; Kartini, Evvy; Drew, Alan J (Journal of Batteries for Renewable Energy and Electric Vehicles, 2024)
Indonesia is at the forefront of the global electric vehicle (EV) battery industry, driven by its rich nickel reserves and strategic initiatives like the National Battery Research Institute (NBRI). This paper explores NBRI’s pivotal role in enhancing skills development within the EV battery sector, a critical factor for sustaining Indonesia's competitive advantage. The study employs a mixed-methods approach, integrating quantitative data analysis with qualitative insights from industry stakeholders. Findings reveal that targeted skills development programs have significantly contributed to workforce readiness, aligning with global trends in green jobs and sustainable energy. However, the industry faces challenges, including the need for continuous upskilling, technological adoption, and collaboration between academia and industry. Opportunities lie in leveraging Indonesia's resource wealth, government policies, and international partnerships to build a robust talent pipeline. The impact of these initiatives is evident in the growth of a skilled labor force capable of driving innovation and sustainability in battery technology. The paper concludes that NBRI’s efforts are crucial in positioning Indonesia as a leader in the global EV battery market, emphasizing the importance of ongoing investment in education and training to meet the evolving demands of this dynamic industry.